Occurrence of some cowpea diseases and the evaluation of resistance of selected cowpea lines to brown blotch disease in the forest ecology of Ghana - Twumasi, J.K.; Hossain, M.A.; Fenteng, P.K. (1990)
Sixty-two IITA and local cowpea lines/varieties were field evaluated without artificial inoculation, for their natural resistance to fungal diseases at fumesus in the forest ecology of Ghana in 1986. Of these, 30 lines were apparently resistant to multiple diseases, 19 were moderately resistant, and 13 susceptible to more than one disease. The most important disease observed were brown blotch, fusarium wilt, target spot, web blight, and anthracnose. Other diseases, of lesser importance included lamb’s tall, pod rot, sclerotium stem rot, and leaf spot/blights caused by various fungi. In 1987, seedlings of 44 cowpea lines/varieties, which had shown apparent field resistance to multiple diseases, were artificially inoculated with colletotrichum truncatum, the causal organism of brown blotch.it was observed that 16 were resistant, 15 moderately resistant, and 13 susceptible to brown blotch